Unlocking the Image of Women in Classic Women's Fiqih Books: A Semiotic Analysis and Its Relevance to the Contemporary Context - Fina Mazida Husna; Sukendar Sukendar; Imam Yahya; Mowafg Masuwd (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
AbstractIn the past, women were limited in their social mobility, which is reflected in various religious jurisprudence texts, incnluding fiqh books specifically written for women. Although these women's fiqh books are considered classic, studies show that they are still the primary references for studying women's fiqh. This research aims to reveal the image of women as depicted by writers of classical women's fiqh books, using semiotic analysis methods. The research question is, what image of women is portrayed by writers of classical women's fiqh books in their works? . The results of the research indicate that the image of women in the classical women's Fiqh book, Risalatul Makhid, depicts the role of women as still normative, which means that women play a major role in the family, as well as being responsible for domestic work. In contrast, Masailun Nisa's book portrays women in a more substantive and prestigious role, allowing them to study and work, and occupy strategic positions in society. However, normative roles are still considered the main role for women.The contribution of this research is to prove the hypothesis that women are still seen as domestic creatures in Islamic boarding school (pesantren) books. Therefore, when teaching students, it is recommended to accompany classical fiqh books with contemporary fiqh discourse that is more humanistic towards women.